Contagion Effect pada Indeks Harga Saham Gabungan dan Jakarta Islamic Index - Jensen, Lukman; Yuliawati, Yuliawati (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2022)
In the current era of globalization, the correlation between macroeconomic variables is certainly getting tighter and harder to separate from one another. This study aims to provide evidence that there is a domino effect or that there is an indirect relationship between international trade proxied to exports and imports to the Composite Stock Price Index (IHSG) and the Jakarta Islamic Index (JII) through intervening interest rates, inflation, exchange rates and the money supply. The test used is the analysis of the Structure Equation Mode (SEM) path. The data used are monthly data on exports, imports, interest rates, inflation, exchange rates, money supply, IHSG and JII during the period February 2013 to December 2018. The results show that there is a domino effect / indirect influence, where exports through inflation and the amount money supply has a negative effect while imports through inflation and exchange rates have a positive effect on the JCI and JII.